Sharia Stock Returns of Infrastructure Companies Listed on the Indonesia Sharia Stock Index - Azizurrahman Nashrullah; Agus Eko Sujianto; Rokhmat Subagiyo (Cahaya Abadi Publisher, 2025)
The development of the Islamic capital market in Indonesia shows a positive trend, supported by an increase in market capitalization and investor confidence in Islamic stock indices such as ISSI. On the other hand, the infrastructure sector has also experienced significant growth as reflected in the increase in the JKINFRA index stock price in recent years. Stock returns as a return on investment are the main concern of investors in assessing a company's performance. This study aims to test the effect of return on equity, current ratio, and debt to equity ratio on stock returns, and to determine whether company size can moderate the relationship between these variables on stock returns. The research method used is quantitative with a multiple linear regression approach and Moderated Regression Analysis (MRA) analysis. The data used are secondary data from the company's financial statements for the period 2020–2023. The results of this study indicate that return on equity and current ratio partially do not have a significant effect on stock returns. Meanwhile, debt to equity ratio has a negative and significant effect on stock returns. Simultaneously, there is an influence between return on equity, current ratio, and debt to equity ratio on stock returns. Company size can strengthen the relationship between return on equity, current ratio, and debt to equity ratio on stock returns.